Mastication force analysis on the fulcrum point of first class lever on lower jaw distal free end denture - Ardan, Rachman (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
The problem in first-class free end lever (distal extension base) Removable Partial Denture (RPD) is the lever force on the retention point that may harm the abutment tooth which has been discussed many times, but the amount of force on the fulcrum point (rest) on the abutment tooth has never discussed yet. The objective of this paper is to analyze the amount of force on the fulcrum point in the first class lever of lower free end denture on the two dimension static models. The analysis result reveals that the force on the fulcrum point is bigger than the mastication force on the free end saddle, or the force on the fulcrum point is equal to the sum of the force of the saddle and the force on the retention point. The force on the fulcrum point may cause trauma to the periodontal tissue of the abutment tooth. To decrease the amount of force on the fulcrum point is by mastication force limitation, decreasing the distance between the mastication point and the fulcrum point; and increasing the distance between retention point and fulcrum point. For clinical application, there are many biological variables to be considered.